Analisis Faktor-Faktor Yang Mempengaruhi Implementasi Kebijakan Pajak Mineral Bukan Logam Dan Batuan Di Kabupaten Wonogiri - Priyono, Patrem Joko; , Drs. M. Farid Wajdi, MM, Ph.D; , Drs. Ahmad Mardalis, MBA (2015)
The purposed of the research to analyzed the influence of the officials service, the accuracy of tax payer data, the accuracy of object tax data, policy implementation and the facilitation toward tax income the non metal mineral and rock in Wonogiri Regency. This research use 100 tax payer as respondents. The technique of collecting data is using questionnaire with Likert scale. Data analysis using multiple regression analysis and classic assumption test. Result of this research indicate that the service of government officer do not have an effect on the positive to implementation of policy mineral lease non metal and rock. Taxpayer accuration do not have an effect on the positive to implementation of policy mineral loease non metal and rock, while accuration of obyect lease have an effect on positive and significant to implementation of policy mineral Iease non metal and rock. While facilitation do not have an effect on positive to implementation of policy of mineral Iease non metal and rock. Examination by simultan (test F) indicating that government officer service, taxpayer accuration, accuration of obyect Iease, and facilitate by simultant have an effect on the significant to implementation of policy mineral Iease non metal and rock.